The Quality of Vehicles' Public Service Testing in The Tomohon Transportation Department - Kalengkongan, Erick Yohanes; Bogar, Wilson; Mamonto, Fitri H. (Technium Social Sciences Journal, 2022)
This study aims to determine the Quality of Public Service Testing of motorized vehicles at the Tomohon Transportation Department. The research method used is qualitative research. Then the data collection techniques are observation, interviews, and documentation with data analysis techniques through data reduction, data presentation, and verification conclusions. This study indicates that the Public Service of Vehicle testing at the Tomohon Transportation Department is not of optimal quality. It is evidenced by the finding problems related to planning, where there is no socialization for program planning. There are processes, mechanisms, and procedures for vehicle testing services. So people do not know about it. They are then related to the instrument where the community does not understand how the mechanism is carried out when testing motorized vehicles. It is also found that the testing service unit when serving the community to complete a task, does not match the predetermined time results in file accumulation. So the community made it to wait, even work. Therefore, the implementing/testing officer or staff should charge the community. It is proven how apathetic the community is and the lack of enthusiasm for the Department of Transportation—providing education to the Public to test their motorized vehicles. The results and targets in the 2021 figures for testing only amount to 337 cars out of 2,333 vehicles. Then it was found that the public response regarding the vehicle testing service was negative, with several things that were felt by the community regarding the services provided. The Department of Transportation was still lacking in Human Resources, which resulted in delays in service and convoluted services. Therefore, it is simplified, but too many stages passed. Furthermore, the services provided by employees to the community are not good services that are not humane and do not communicate well. Problems were also related to infrastructure that was no longer suitable for use.